2020
DOI: 10.1177/0308518x20903728
|View full text |Cite
|
Sign up to set email alerts
|

The geographies of intermediation: Labor intermediaries, labor migration, and cane harvesting in rural western India

Abstract: In this paper, I explain the role of labor intermediaries in the weaving of capital–labor relations in capitalist agro-business. I do so by focusing on migration infrastructure or the vertical network of labor intermediaries who facilitate labor recruitment from migrant home villages and migrant labor disciplining on cane fields in rural western India, where the laborers are brought seasonally to harvest sugarcane. I show how the role of labor intermediaries cannot be understood by containing them within the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This normative view of migration industry activities reinforces neat but problematic dichotomies between free/unfree or voluntary/ involuntary migration (Cuttitta, 2018;Erdal and Oeppen, 2018;McKeown, 2008) while ignoring the extent to which migration agents, brokers, recruiters, even traffickers are part of wider social networks where the lines between victimisation and altruism can be blurred (Rai, 2020). It is, for example, commonly observed that brokerage practices enhance the precarity of migrants (Lindquist et al, 2012) but through enabling mobility and cultivating aspirations, intermediaries also create space for agency, making mobility possible even if at a cost; 'subjectivation/precarisation and agency should not be examined as two opposing poles but rather as an inherent part of the migration process where one cannot be separated from the other' (Deshingkar, 2019(Deshingkar, : 2639.…”
Section: Migration Industriesmentioning
confidence: 97%
See 1 more Smart Citation
“…This normative view of migration industry activities reinforces neat but problematic dichotomies between free/unfree or voluntary/ involuntary migration (Cuttitta, 2018;Erdal and Oeppen, 2018;McKeown, 2008) while ignoring the extent to which migration agents, brokers, recruiters, even traffickers are part of wider social networks where the lines between victimisation and altruism can be blurred (Rai, 2020). It is, for example, commonly observed that brokerage practices enhance the precarity of migrants (Lindquist et al, 2012) but through enabling mobility and cultivating aspirations, intermediaries also create space for agency, making mobility possible even if at a cost; 'subjectivation/precarisation and agency should not be examined as two opposing poles but rather as an inherent part of the migration process where one cannot be separated from the other' (Deshingkar, 2019(Deshingkar, : 2639.…”
Section: Migration Industriesmentioning
confidence: 97%
“…Brokerage, thus, entails establishing platforms that actively work on the character of migration -establishing pathways or trajectories for migrants through complex systems (Collins, 2020;Wee et al, 2019), negotiating and managing labour relations and debt financing (Baey and Yeoh, 2018;Moniruzzaman and Walton-Roberts, 2018) as well as through cultivating conceptions of the ideal migrant/worker (Awumbila et al, 2019;Collins and Bayliss, 2020;Deshingkar, 2019;Picherit, 2019). The figure of the broker is often framed in moralistic terms, an actor who seeks profit through inducing, deceiving and victimising migrants while simultaneously disrupting the intent of state control of migration (Deshingkar, 2019;Rai, 2020).…”
Section: Migration Industriesmentioning
confidence: 99%
“…The final section is comprised of papers that examine informal, often micro-sized and migrant-driven migration industries that nonetheless provide services for primarily vulnerable migrants uncatered to by the more intentional, institutionalised migration industries. Focus on such providers highlights how commercialised provision of services is often intertwined with or arises within and through spaces of migrants’ social networks, problematising earlier dualistic framing of pure for-profit migration industries on one hand and altruistic social networks on the other (Jones and Sha, 2020; Rai, 2020). But more importantly in relation to their urban dimensions, they highlight the city as an often-unwelcoming space of arrival, whether for those sojourning temporarily or more long-term.…”
Section: Migration Industries Andcity-making: Key Vantage Pointsmentioning
confidence: 99%
“…Although much is known about drivers of migration and migrants' experiences abroad, less is known about the stages in-between and the actors within this space -the black box encompassing 'institutions, networks and people that move migrants from one point to another' (Lindquist et al, 2012: 9; see also McCollum and Findlay, 2018). Recruitment agents 1 play an integral role in the international labour supply chain (Battistella, 2014;Cranston et al, 2018;Enright, 2013;Gordon, 2015;McCollum et al, 2013;Rai, 2020). They provide information on employment opportunities, act as mediators between parties and assist migrant workers in meeting various regulatory requirements where they perform as 'bureaucratic circumnavigators' (Wee et al, 2020: 2; see also Asis et al, 2019;Gordon, 2015).…”
Section: Introductionmentioning
confidence: 99%